1992
DOI: 10.1007/bf01624143
|View full text |Cite
|
Sign up to set email alerts
|

Spinal fractures during fluoride therapy for osteoporosis: Relationship to spinal bone density

Abstract: Recent studies report that fluoride therapy for osteoporosis increases spinal bone density without improving vertebral fracture rate, challenging the notion that restoration of bone mass improves bone fragility. To further evaluate this issue, the relationship between spinal bone density and vertebral fracture rate was examined in a large number of fluoride-treated, osteoporotic patients. A retrospective assessment was made of clinical data collected from our observations of 389 osteoporotics treated with fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…NaF is so far the most potent stimulator of bone formation that has been used clinically (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)45). In spite of clearcut increases in bone mass, the effect of fluoride treatment on osteoporotic fractures is equivocal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NaF is so far the most potent stimulator of bone formation that has been used clinically (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)45). In spite of clearcut increases in bone mass, the effect of fluoride treatment on osteoporotic fractures is equivocal.…”
Section: Discussionmentioning
confidence: 99%
“…There are conflicting reports on the effect of NaF treatment on fracture rates in osteoporotic patients (recently reviewed in references 6 and 7): some studies found no reduction or even an increase ( 8-1I1 ), whereas others showed a significant reduction in fracture rate (12)(13)(14)(15)(16). These differences have been attributed to the NaF dose (17), which was higher in studies in which treatment did not reduce the incidence of fractures (18).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, this consistent anabolic effect on bone mass has not invariably been found to be associated with an increase in bone strength. Indeed, the fracture rate has been found to be either decreased or uninfluenced or still increased by fluoride treatment [52,[55][56][57][58][59][60][61]. Several possible explanations have been proposed for the discrepancy, among them the severity of osteoporosis at the beginning of treatment, the absolute daily doses, the dosing schedule, and the duration of treatment [62].…”
Section: Predictive Value Of Preclinical Studiesmentioning
confidence: 95%
“…Despite the current controversy regarding fluoride and fracture prevention, clinical data indicate that fluoride is the single most effective agent currently available for increasing bone volume in the osteoporotic skeleton [1][2][3][4][5][6][7][8][9][10]. Histomorphometric analyses have shown that fluoride increases bone Offprint requests to: J. R. Farley volume by increasing the bone-forming surface [10][11][12][13], and in vitro data have further suggested that this increase in osteoblast number may be mediated by direct effects of fluoride on osteoblast-like cells [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%